Pengawasan Terhadap Penggunaan Kendaraan Dinas di Instansi Pemerintah - I Komang Roni Januar; Ida Ayu Widiati; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2020)
The Indonesian state adheres to the Presidential system of government. In running the government, a president is assisted by his staff. We call this line of government. The government that we often know as Civil Servants. The position of civil servants has an important role carrying out government functions in a country. Based on this there are formulations of the problem as follows: (1) How to regulate the use of official vehicles in government agencies (2) How to monitor the use of official vehicles in Government Agencies. This type of research used is the type of normative legal research, the discussion conducted by the study of legal materials. Analysis of legal material uses legal interpretation, namely providing interpretation in terms of law. Based on the results of the study that regulations related to the use of official vehicles in government agencies are regulated in ministerial regulations and further regulated by each region in the form of governor regulations or regional regulations and Supervision of vehicle use in government agencies is carried out by Direct and Indirect Supervision . In addition to paying attention to the products of the laws and regulations, also pay attention including official vehicles, are not misused.